Design, preparation and evaluation of a certain phosphodiesterase (PDE5) inhibitor in solid dosage forms - Karim Aboubakr Mohamed Mohamed Soliman; Howida Kamal Ibrahim; Mahmoud Mohammed Ghorab (Cairo : Karim Aboubakr Mohamed Mohamed Soliman, 2016)
vanafil is an inhibitor of phosphodiesterase enzyme type 5 (PDE5). It was approved for treatment of erectile dysfunction by US Food and Drug Administration on April 2012, and by European Medicines Agency on June 2013. It is characterized by its rapid onset of action and it exhibits visual side effects to a lesser extent than other PDE5 inhibitors. It is poorly soluble in water and has relatively low bioavailability of 38%{u2013}41%. Its oral bioavailability could be increased by improving its aqueous solubility using different techniques. These include nanocrystallization, inclusion complexation and nanoemulsification
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Pharmaceutics
Issued also as CD
Keywords: Canines; Maxillary and Mandibular; Permanent Mandibular Incisors